1978
DOI: 10.1111/j.1399-3054.1978.tb08624.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Control of Ripening in Banana

Abstract: A post harvest dip of banana (Musa paradisiaca L.) fruits into the aqueous solutions of abscisic acid and indoleacetic acid significantly hastened the banana ripening, judging from increases in total sugars, acidity, ascorbic acid and units of von Losecke's colour chart during storage at 20°C. The treatment of bananas with gibberellic acid and kinetin, on the contrary, retarded banana ripening as indicated by higher values for firmness, starch, cellulose and hemicellulose. The results obtained suggest that rip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Similar results were reported duringripening of banana (Ahmed and Tingwa, 1975;Desai & Deshpande, 1978) and mango (AbuGoukh and Abu -Sarra, 1993).This sizable decrease in TA could be attributed to its use as a substrate for respiration. Coated fruits, showed the higher flesh acid content value (Table 7).…”
Section: Titratable Aciditysupporting
confidence: 75%
“…Similar results were reported duringripening of banana (Ahmed and Tingwa, 1975;Desai & Deshpande, 1978) and mango (AbuGoukh and Abu -Sarra, 1993).This sizable decrease in TA could be attributed to its use as a substrate for respiration. Coated fruits, showed the higher flesh acid content value (Table 7).…”
Section: Titratable Aciditysupporting
confidence: 75%
“…Cellulose metabolism has been implicated as an important feature of fruit softening in apple (Abeles and Biles 1991), peach (Hinton and Pressey 1974) and avocado (Pesis et al 1978). In Dwarf Cavendish hanana, Desai and Deshpande (1978) also reported that the cellulose content continued to decrease daring ripening. However, our results show that the cellulose content is constant during ripening.…”
Section: Discussionmentioning
confidence: 91%
“…However, only a few investiga- Brady 1987, Huber 1983a, There is evidence that soft-tors measured the degradation of cell wall components ening of fruit is accompanied hy an increase in the con-such as pectin (Marriott 1980, Wade 1992, hemicellulose centration of soluble pectic polysaccharides. However, (Bamell 1943, Desai andDeshpande 1978) and cellulose considerahly less is known regarding the role of cell wall (Desai and Deshpande 1978) during the ripening propolymers other than the polyuronides in fruit softening.…”
mentioning
confidence: 99%
“…A dip in IAA solution at 100 ppm for 10 minutes initiated ripening, as did a dip in 10 ppm for 30 minutes . However a dip in 200 ppm for 5 seconds had no effect [12,13] . The seemingly contradictory effect on ripening of whole fruits and of slices, as demonstrated for 2,4-D, was also observed with IAA : ripening of whole fruit was accelerated and that of slices delayed .…”
Section: Effect On Fruitmentioning
confidence: 99%
“…The delay in ripening is accompanied by a slowdown in the rate of changes occurring during ripening, such as degreening, decreasing acidity, increasing levels of ascorbic acid and of sugars, as well as loss of firmness, starch, cellulose and hemicellulose [3,4,13,24,37] . Furthermore, the activity of some enzymes, such as alpha-amylase, starch phosphorylase, acid phosphatase, peroxidase and catalase is reduced [13,14] . A dip in 500 ppm for 45 minutes augmented the delaying effect, especially on the peel, which remained green long after softening of the pulp [19] .…”
Section: Effect On Fruitmentioning
confidence: 99%